Constrained Peptides with Fine‐Tuned Flexibility Inhibit NF‐Y Transcription Factor Assembly. Issue 48 (17th October 2019) - Jeganathan, Sadasivam; Wendt, Mathias; Kiehstaller, Sebastian; Brancaccio, Diego; Kuepper, Arne; Pospiech, Nicole; Carotenuto, Alfonso; Novellino, Ettore; Hennig, Sven; Grossmann, Tom N.
Abstract: Protein complex formation depends on the interplay between preorganization and flexibility of the binding epitopes involved. The design of epitope mimetics typically focuses on stabilizing a particular bioactive conformation, often without considering conformational dynamics, which limits the potential of peptidomimetics against challenging targets such as transcription factors. We developed a peptide‐derived inhibitor of the NF‐Y transcription factor by first constraining the conformation of an epitope through hydrocarbon stapling and then fine‐tuning its flexibility. In the initial set of constrained peptides, a single non‐interacting α‐methyl group was observed to have a detrimental effect on complex stability. Biophysical characterization revealed how this methyl group affects the conformation of the peptide in its bound state. Adaption of the methylation pattern resulted in a peptide that inhibits transcription factor assembly and subsequent recruitment to the target DNA. Abstract : Set Me free : A peptide‐derived inhibitor of the NF‐Y transcription factor was developed by constraining the conformation of an epitope through hydrocarbon stapling and then fine‐tuning its flexibility. In the initial set of constrained peptides, a non‐interacting α‐methyl group was observed to have a detrimental effect on complex stability. Adaption of the methylation pattern gave a peptide that inhibits transcription factor assembly and subsequent DNA binding.